2020
DOI: 10.1111/geb.13217
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in plant defence against herbivory in a marine foundation species does not follow a linear pattern: The importance of resource availability

Abstract: Aim: Studies on latitudinal patterns in plant defence have traditionally overlooked the potential effect that resource availability may have in shaping plant defence. Likewise, latitudinal patterns of tolerance traits have rarely been studied, yet they can be a critical component of plant defence. Therefore, the aim of our study was to examine latitudinal variation in the production of tolerance and resistance traits against herbivory along a latitudinal range and a natural gradient of resource availability fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 95 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…This follows our hypothesis and aligns with previous nutrient enrichment studies in salt marshes (Johnson et al 2016, Li et al 2017, Crosby et al 2021, Moore et al 2021). Interestingly, in two other studies that evaluated the RAH in seagrasses, elevated nutrient availability decreased defensive traits yet had no effect on growth (Hernán et al 2019, 2021). The authors attributed this result to a potential limiting resource other than nitrogen (e.g.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This follows our hypothesis and aligns with previous nutrient enrichment studies in salt marshes (Johnson et al 2016, Li et al 2017, Crosby et al 2021, Moore et al 2021). Interestingly, in two other studies that evaluated the RAH in seagrasses, elevated nutrient availability decreased defensive traits yet had no effect on growth (Hernán et al 2019, 2021). The authors attributed this result to a potential limiting resource other than nitrogen (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, low stress environments with high resource availability facilitate and support higher herbivore abundances and thus grazing pressure, causing plants in these areas to have greater constitutive defense, a pattern opposite of the RAH (Hahn and Maron 2016, López‐Goldar et al 2020). Since the development of the RAH intra , both hypotheses have been applied in various ecosystems (seagrasses: Hernán et al 2019, Hernán et al 2021; deciduous forests: Lynn and Fridley 2019; pine forests: López‐Goldar et al 2020; grasslands: Hahn et al 2021), with mixed support for each hypothesis, suggesting that whether the RAH or the RAH intra predicts plant response to herbivory may be ecosystem‐dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In grasslands, a manipulative experiment across 40 sites and six continents found that nutrient additions reduced plant diversity, but herbivores rescued diversity in these areas (Borer et al 2014b). In seagrass beds, a manipulative experiment across 20 degrees of latitude found that resource availability influenced plant defenses (Hern an et al 2020). The significant replication of these experiments across sites provided a robust assessment of the roles of resources and herbivory on plants.…”
Section: Introductionmentioning
confidence: 96%
“…For example, nitrogen and phosphorus enrichment were found to increase sucrose contents in Enhalus acoroides leaf (Artika et al, 2020), but sucrose contents of Halophila stipulacea and Posidonia oceanica leaf were observed unchanged and decreased after nitrogen and phosphorus additions, respectively (Pazzaglia et al, 2020;Helber et al, 2021b). Previous studies reported that nutrient loading could change the LOC content of seagrass plants (Brun et al, 2002;Touchette and Burkholder, 2007;Jime ́nez-Ramos et al, 2017;Artika et al, 2020;Herna ́n et al, 2021). However, there is still little information on seagrass ROC changes in response to nutrient loading.…”
Section: Introductionmentioning
confidence: 97%